Akhlak Dalam Kehidupan Modern - Surianti .; Rizky Nurawalia Mansur; M. Amin (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Morality (akhlaq) constitutes the core of Islamic teachings and serves as a guiding principle in shaping the complete personality of human beings. In the modern context, moral values are often eroded by technological advancement, globalization, and rapid social change. This study aims to examine in depth the concept of akhlaq in Islam, its theological and philosophical foundations, and its relevance in education and contemporary social life. The approach employed in this research is descriptive-analytical, through the examination of classical and contemporary literature. The findings indicate that Islamic morality is derived from the Qur’an, Hadith, and the thoughts of scholars such as Al-Ghazali and Ibn Miskawayh, who emphasize the balance between reason, the heart, and actions. In the modern era, akhlaq plays a central role in shaping the character of the younger generation to be individuals of integrity, empathy, and adaptability in facing the developments of the time. Moral education thus becomes essential in addressing moral degradation caused by hedonism, individualism, and digital disinformation.